Pembentukan Karakter Religius Dalam Kegiatan ShalatDhuha Dan Zuhur Berjamaah Di Sd Muhammadiyah 3Nusukan Surakarta Tahun Ajaran 2016-2017 - Lestari, Yuni, Honest Ummi Kaltsum, S.S.,M.Hum (2017)
This study aims to describe: 1) Implementation of Dhuha and Zuhur prayer activities at Muhammadiyah 3 Nusukan Surakarta Basic School. 2) the formation of religiouscharacters in the students of Primary School Muhammadiyah 3 Nusukan Surakarta. The method of this research is qualitative research, the design of this research isqualitative descriptive. The place of this research was conducted at Muhammadiyah3 Nusukan Surakarta Elementary School. Data collected are data from interviews,observation data and documentation data. The sources and data sources in thisresearch are principal, third grade teacher, fourth grade teacher, class V teacher, grade 6 teacher. Data collection techniques used were interviews, observation, anddocumentation. Data were analyzed using interactive analysis model through three steps: data reduction, data display, and conclusion. The technique of examining thevalidity of data is done by using triangulation technique and source triangulation.The results of this study show that: 1) Duha prayer activities are held at nine o'clock.Carried out in congregation. Followed by teachers and students of class III, IV, V,and VI. Prayer activities dhuha headed by students, while the prayer zuhur headedby teachers. 2) SD Muhammadiyah 3 Nusukan Surakarta already has religiouscharacter such as: obedient to perform the prayer, mutual help, do good, tolerance,calm, serene, happy, gratitude, and obedient.